FINANCING DISTRIBUTION AND ITS EFFECT ON NON-PERFORMING FINANCING OF ISLAMIC BANKS - Saputri, Pungky Lela; Ahmadi, Hanif (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2022)
Non-performing financing manifested in the Non-Performing Financing (NPF) ratio is a threat to the sustainability of Islamic banks. This research seeks to reveal how much financing distribution carried out by Islamic banks can have an impact on NPF through hypothesis testing. This study examines the variables of profit-sharing financing and murabahah financing to the NPF ratio of Islamic banks. Timeseries data from each of these variables is obtained from the Quarterly Financial Statements of Bank Syariah Indonesia for the period 2015 – 2022. The data were tested using multiple linear regression. The results of the study found that profit-sharing-based financing turned out to be profit-sharing-based financing able to suppress the occurrence of NPF and murabahah financing had no influence on increasing NPF.